Potencial terapêutico do grupo de artesanato no cuidado a mulheres na atenção básica - Scardoelli, Márcia Glaciela da Cruz (2009)
Several situations in human day-to-day life cause turmoil in the subject's mental health. When the latter is unprepared for overloads of stressing factors they will bring about behavior changes which, if not perceived, understood or accepted within the family context, affect relationships among family members. Current research aims at understanding the motives that cause subjects to integrate artisan groups as a prop for their mental health, the meaning of group participation and its influence on family relationship. This fact may help them to seek a mechanism or a support basis that would make them find a new path to face and adapt themselves to unexpected events. Thus, group space may be used as a tool with a therapeutic potential for the mental state against a return to pain conditions. Psychic ailment is consequently avoided. A descriptive research with eleven females was undertaken and featured participatory observation and qualitative approach with regard to an artisan group of a Health Basic Unit in the municipality of Maringá PR Brazil, between March and August 2009. Data collection techniques comprised participatory observation, systematically reported in a field diary, and an open interview carried out at the subjects' home. Data were analyzed according to Bardin, coupled to organization of analysis, codification and categorization by the identification of themes: a space for the promoção and rehabilitation of mental health; Finding a space that promotes speaking, listening and sharing; seeking a space to attend to real needs; the precious stones that we meet in our path; changes perceived with regard to one self and reflected in familial conviviality. Results showed that the artisan group represented a solution from tedious routine life, moments of leisure and a rupture from the tensions caused by daily problems. Further, the artisan group was counterpoised to the extenuating and stress context which the female participating subjects experienced, or rather, a way to experience a period of creativity, leisure, occupation of space and time, distraction and laughter. In fact, it was experienced as a period dedicated to self-care and a better life quality which directly affected the maintenance of mental health. The recovery of self-esteem and self-confidence was important so that the female subjects could live a different type of life. In fact, their identities had been lost owing to unexpected situations they were experiencing when they started to participate in the group. Group conviviality made these women perceive changes in behavior which affected their way of thinking, acting and reacting in the wake of common day-to-day situations. It also made them think on the respect one must have with regard to the individuality of the other so that they could live harmoniously and healthily within the family. The participants' perceptions on group meetings also showed an improvement in family relationships which caused a significant approach, agreement and communication among the members. This fact was also perceived by members of the family who continued their support so that they could further their participation in the group. Exchange of life experience among the female subjects was a lively factor that made possible the acquisition of important knowledge and information according to the needs of each one so that a certain type of behavior could be acquired or changed. The artisan group showed up to be not a mere leisure as many believed but a factor of paramount important. In fact, transformation through the conviviality with other people became possible. A new meaning to the subjects' life was thus provided when prior to the event their lives was full of anxiety, sadness, loneliness and lacking expectation of any solutions to face their woes. The artisan group within the prospect of mental health is a strategy which contributes towards favorable and healthy conditions for an improvement in life quality and, consequently, the maintenance and re-equilibrium of the female subjects' mental health. It is highly important to discover other ways of mental health care so that other people who suffer and need care prior to their sickness may be accepted. This fact may be found in the interview answers as one of the motives that caused some of the female subjects to integrate themselves in the artisan group to lessen their anxieties and unhappiness found in the daily course of their lives. Carrying out activities within a group is an important strategy that should be employed by health professionals, especially by nurses, for the development of activities to promote mental health as basic care. Current analysis showed the importance of group space and its positive influence in the life of the subjects. In fact, it directly affected one's relationship and the relationship with other people in their lives. Direct influence in the maintenance of the subjects' mental health has been successfully perceived.